Quality and cost in health care choice in developing countries - Lavy, Victor; Germain, Jean-Marc. (Washington, D.C. : World Bank, 1994)
This study contributes to our understanding of the effect of quality improvement on demand, and explores the implications for the use of user fees in the public health sector. It is part of a broader research effort on the Policy Research Department that examines the effect of the quality of social services on human capital investment outcomes.
Includes bibliographical references: p. 31-33.
ne 18/03/2019
Loans
Keywords: Medical care, Cost of; Medical care---Utilization.; Health services accessibility; Medical care---Finance.; Consumer behavior; Medical care---Public opinion